Atributos do solo e nutrientes em folhas de café conilon no tabuleiro costeiro do Espírito Santo - Pires, Ivne Franco (2019)
Coffee cultivation is one of the activities of great profitability in Espírito Santo and with extensive occupation of the Coastal Tablelands, whose geomorphological unit includes soils with low levels of nutrients and cohesive subsurface horizons. In view of the above, the objective of this work was to provide a diagnosis of the physical and chemical attributes of the soil and nutritional status of the leaves of the Conilon coffee tree in Oxisols and Yellow Argisols in Coastal Trap environments of the northern region of Espírito Santo, relating the methods of soil and leaf analysis with non-destructive techniques such as X-ray fluorescence spectrometry. The samples were collected in the municipalities of São Mateus, Jaguaré, Boa Esperança, Pinheiros, Conceição da Barra and Montanha. Soil physical analyzes were performed to determine the grain size composition, soil density, particle density and total porosity. In the soil chemical analyzes the active acidity (Al3+), Ca2+, Mg2+, K+ , potential acidity (H+Al), SB, V, CTC, pH in water, Mehlich-1 phosphorus, organic carbon, organic matter, nitrogen and micronutrients (Cu2+, Fe2+, Mn2+, Zn2+). Macronutrients and micronutrients were determined on leaves. The soil fertility and leaf nutrition were diagnosed, identifying the deficit elements, comparing them with reference coffee crops in studies conducted ix in the State of Espírito Santo. Leaf and soil chemical analyzes were also performed using a non-destructive technique based on X-ray fluorescence spectrometry using portable equipment, using two calibration methods from the factory: Soil and Geochem. Pearson's linear correlation and Student's t test methods were analyzed. Regarding the physical attributes of the soil, most of the crops present density of 1.43 g cm-3 and loamy-clayey texture. Regarding routine chemical analyzes, the values of OM, K, Ca, Mg, Fe, Al and (H+Al) were classified with low levels in the soil, excess P and other attributes at medium levels. In the leaf analyzes the N, P, K, Mg, Cu, Fe and Zn levels were classified as low levels in the plants, Ca presents high levels, only the Mn content is at an adequate level. There is no tendency to increase the nutrient content in the leaves with the increase of the same in the soil, indicating that there is no direct relation. When compared to reference crops, most of the soil elements, except for P, Ca and Zn, are at lower levels and all leaf elements are at lower levels, with emphasis on Fe and Mn. As for the X-ray fluorescence spectrometry analyzes, the soil nutrient values found in the pXRF analysis were underestimated when compared to the certified values, all with low recovery rates. In the leaf analysis, the calibration methods presented values that were overestimated in relation to the values obtained by the routine chemical analysis, the smallest difference was for K in the "Soil" method and higher for the P in "Geochem", where Soil "Presents values closer to the traditional method. There is a statistical difference between the conventional leaf analysis method and the X-ray fluorescence methods by the 5% probability t test and the correlations between the nutrient levels in the methods used are significant, indicating the potential use of the tool.